Ventricular tachycardia channels ablation incorporating automated high-density mapping guidance: data from the CHARISMA registry. (19th May 2022) - Battaglia, A; Calvanese, R; Pandozi, C; Tola, G; Solimene, F; Rossi, L; Cauti, F; Pedretti, S; Mantovan, R; Pelargonio, G; Castro, A; Gagliardi, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Ventricular tachycardia (VT) ablation targeting conducting channels (CC)s based on timing of late potentials (LPs) during sinus rhythm (dechanneling) may facilitate a scar homogenization strategy without the need for extensive ablation and possibly lead to higher successful rate. Purpose: We evaluated the feasibility and safety of a CC identification and ablation approach by means of an ultra-high density mapping system with a novel automated algorithm in ischemic VT procedures. Methods: Consecutive patients indicated for ischemic VT ablation were prospectively included. A complete map of the left ventricle was performed prior and after ablation through the Rhythmia mapping system. Channels were defined as any signal activity bounded by anatomic and functional barriers and characterized through the Lumipoint (LM) tool and continuous activation was used on the whole ventricular substrate. Procedural end point was the elimination of all identified CCs by ablation at the CC entrance and exit followed by abolition of any residual LPs inside the CC. The ablation endpoint was noninducibility. Data are reported as mean±SD. Results: A total of 36 channels were identified through LM from 28 patients (1.2±0.5 per patient): 21 (75%) patients had 1 CC, 6 (21.4%) had 2 CCs and 1 (3.6%) had 3 CCs. LPs were identified inside CCs in 19 cases (67.9%). In 8 cases (28.6%) LPs were present both inside and outside and in 1 (3.6%) case LPs were present only outside the CC. LPs inside channels covered an area of 7.6±5 mm2 with a ratio between LPs area and CCs' area of 67.4±31.8%. In 12 (43%) cases LPs area covered more than 90% of the CCs' area. At voltage map analysis a total of 34 CC were identified: 1 CC was present in 75% of the cases, 2 CCs in 17.9% and 3 CCs in 3.6%. LPs were identified only inside CCs in 46.4% of the cases, both inside and outside in 42.9% and only outside in 10.7%. Healthy tissue (voltage level≥0.5mV) was prevalent (68.2±17%), followed by intermediate voltage areas (0.5-0.05 mV; 31.1±17%) and very low voltage areas (<0.05mV; 0.7±1%). LPs were found mostly at intermediate voltage areas (57.0±34% of the covered area; 39.1±33% at healthy tissue and 3.4±13% at very low voltage areas). LM was more accurate than traditional voltage mapping in identifying CCs: in 6 (21.4%) cases voltage map overestimated LPs areas, in 2 (7.1%) cases failed to fully identify LPs and only in 19 out 28 (67.8%) LM and voltage map had a complete agreement. All CCs' entrance and exit were successfully ablated and abolition of any residual LPs inside the CC was achieved in all patients. No complication occurred. Noninducibility was achieved in all (100%) the cases. Conclusions: In this experience, a channel identification approach through the advanced Lumipoint tool was more accurate than traditional voltage mapping and seems to be safe, feasible, and effective at least in the acute setting of ischemic VT ablation.